Association between Acute and Chronic Inflammatory States: A Case-Control Study - Mahesh, Seema; Mallappa, Mahesh; Vacaras, Vitalie; Shah, Viraj; Serzhantova, Elena; Kubasheva, Nadezhda; Chabanov, Dmitriy; Tsintzas, Dionysios; Jaggi, Latika; Jaggi, Atul; Vithoulkas, George (Homeopathy, 2024)
Background Fever is the hallmark of efficient acute inflammatory response, which may be disrupted in chronic inflammatory conditions. The “continuum theory” proposes that the return of acute inflammatory states with high fever predicts improvement in chronic diseases during treatment. Our objective was to investigate the observation made, during classical homeopathic treatment, that such an association exists between chronic inflammation and efficient acute inflammation.Methods In a case-control study, the reports of patients diagnosed with chronic inflammatory conditions with at least 6 months of follow-up under homeopathic treatment were retrospectively sampled from homeopathic medical practices from Greece, India, Romania and Russia. Twenty patients who improved under homeopathic treatment and 20 age-matched controls of those who did not improve were selected. The occurrence of common acute infectious diseases with fever during the follow-up period was investigated.Results The average age of the cases and controls was 28.4 (SD: 16.64) and 27.9 (SD: 17.19) years respectively. 18/20 cases and 4/20 controls developed common infectious diseases with fever. Cramer's V co-efficient value was found to be 0.551 (p < 0.01), indicating that improvement was more in patients with fever than without. Odds ratio of improving with respect to development of acute infectious diseases was 36.0 (95% CI: 5.8 to 223.5). The binary logistic regression model indicated significant contribution of occurrence of acute infections with fever as a predictor for improvement in chronic inflammatory disease.Conclusions Classical homeopathic clinical observations indicate an association between chronic inflammatory status in the body and the ability to mount efficient acute inflammation. In this case-control study, the occurrence of common infections with fever during treatment heralded improvement in chronic inflammatory disease. Further powered studies are necessary to substantiate this finding.
Keywords: inflammation; fever; homeopathy